Gut Microbiome and Autism: Recent Advances and Future Perspectives - Liu, PhD, Jun; Zhang, PhD, Mei; Kong, MD, Xue-Jun (North American Journal of Medicine and Science, 2016)
Autism spectrum disorder (ASD) is a complex neurological and developmental disorder characterized by impaired communication and social interaction skills, as well as stereotypical repetitive behavioral patterns. Its etiology remains elusive, likely involving a combination of genetic changes and environmental factors. Among them, microbiome dysbiosis of the gastrointestinal (GI) system and its effect on CNS inflammation appears to be an important one. Symptoms of the GI system in patients with ASD are closely associated with primary or secondary changes in microbiome abnormalities of the gut. Moreover, the severities of neurological and behavioral symptom in ASD are determined at least in part by gut microbiome profiles in some subgroups of ASD patients. We review the evidence supporting notions of microbiome dysbiosis in host pathogenesis, especially with respect to diseases of the central nervous system (CNS). Next, we explore the differences in gut microbiome between neurotypical and ASD children, how these differences arise and how alterations in gut microbiome can lead to the pathogenesis or exacerbation ASD symptoms. We also attempt to address current and emerging new strategies of ASD therapeutic interventions that aim at modulating the gut microbiome, including dietary therapies/prebiotics, probiotics/antibiotics, fecal microbiota transplantation, immune therapies, and the use of traditional Chinese medicine. [N A J Med Sci. 2016;9(3):104-115. DOI: 10.7156/najms.2016.0903104]